A Rare Case of the Simultaneous, Multifocal, Metastatic Renal Cell Carcinoma to the Ipsilateral Left Testes, Bladder, and Stomach. (21st January 2016) - Kongnyuy, Michael; Lawindy, Samuel; Martinez, Daniel; Parker, Justin; Hall, Mary
Abstract : We describe the rare case of a 68-year-old gentleman with the history of a hand-assisted laparoscopic left radical nephrectomy for a T2bN0M1 clear cell renal cell carcinoma (RCC). Seven years after surgery and with clean surveillance imaging for metastasis/recurrence the patient presented with three separate tumors suspicious for malignancy. A bladder lesion was found during workup for hematuria, a stomach lesion during diagnostic endoscopy, and a testicular lesion during self-exam. He underwent transurethral resection of bladder tumor, left inguinal orchiectomy, and upper endoscopic ensnarement. All specimens surprisingly showed RCC by histology and immunostaining. These three sites are rare for RCC metastasis and simultaneous presentation is even rarer, further emphasizing the importance of continuous and careful follow-up in this patient population, despite what could appear as complete remission.